CELL CYCLE-SPECIFIC CHANGES IN HISTONE PHOSPHORYLATION ASSOCIATED WITH CELL PROLIFERATION AND CHROMOSOME CONDENSATION - Gurley, Lawrence R. (The Rockefeller University Press, 1974)
Preparative polyacrylamide gel electrophoresis was used to examine histone phosphorylation in synchronized Chinese hamster cells (line CHO). Results showed that histone f1 phosphorylation, absent in G(1)-arrested and early G(1)-traversing cells, commences 2 h before entry of traversing cells into the S phase. It is concluded that f1 phosphorylation is one of the earliest biochemical events associated with conversion of nonproliferating cells to proliferating cells occurring on old f1 before synthesis of new f1 during the S phase. Results also showed that f3 and a subfraction of f1 were rapidly phosphorylated only during the time when cells were crossing the G(2)/M boundary and traversing prophase. Since these phosphorylation events do not occur in G(1), S, or G(2) and are reduced greatly in metaphase, it is concluded that these two specific phosphorylation events are involved with condensation of interphase chromatin into mitotic chromosomes. This conclusion is supported by loss of prelabeled (32)PO(4) from those specific histone fractions during transition of metaphase cells into interphase G(1) cells. A model of the relationship of histone phosphorylation to the cell cycle is presented which suggests involvement of f1 phosphorylation in chromatin structural changes associated with a continuous interphase "chromosome cycle" which culminates at mitosis with an f3 and f1 phosphorylation-mediated chromosome condensation.